Sustainability Reporting, Foreign Ownership, Firm Value as a Function of Investment Opportunity Set - Vanisa Nur Hasanah; Elva Nuraina; Farida Styaningrum (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: Firm value is one of the relevant company goals. Increasing firm value is supported by sustainability reporting and foreign ownership. The increase in firm value can be strengthened through a trusted Investment Opportunity Suitable to obtain returns that are attractive to investors and can be used as an injection of funds to implement sustainability reporting. Investigating the Investment Opportunity Set role in moderating the effect of sustainability reporting and foreign ownership on firm value. This study aims to investigate the Investment Opportunity Set in moderating the effect of sustainability reporting and foreign ownership on firm value.Method: This study uses a quantitative approach with independent variables on sustainability reporting and foreign ownership, the dependent variable on firm value, and the moderating variable. Investment Opportunity Set. This research is classified as non-experimental with cross-sectional data classification and documentation method. The research sample was 46 companies from 606 companies listed on the Indonesia Stock Exchange for 2013-2018. This study uses regression and Moderated Regression Analysis.Findings: The results showed that the Investment Opportunity Set does not moderate the effect of sustainability reporting on firm value. But Investment Opportunity Set moderate the influence of foreign ownership on firm value. Novelty: This study develops from previous research by proving that foreign ownership based on foreign investors is able to increase firm value. The study was conducted in all companies listed on the IDX that publish annual reports and sustainability reporting for the 2013-2018 period, this period is determined based on the first year of the change from the GRI G3 version to GRI G4 on May 22, 2013 which was launched in Amsterdam at the global sustainability reporting conference.